NC simulation with dynamic errors due to high-speed motion - Yau, H.-T.; Ting, J.-Y.; Chuang, C.-M. (International journal of advanced manufacturing technology, 2004)
Traditional NC simulation has not always considered dynamic contouring errors in machining when simulating a tool path. For instance, if the feed rate is high, the effect of dynamic machining errors will be apparent on the work piece, but traditional NC simulation does not account for the dynamic errors at all. Due to the increasing demand of reducing product cycle time, high-speed machining of dies and moulds are becoming more and more popular. Under high-speed motion, over-cut or gouging can easily occur even when traditional NC simulation proves that the NC path is correct. Therefore, it is of significance to be able to predict dynamic machining errors in NC simulation before the part is machined, especially under high-speed motion. This paper presents the simulation of NC machining with dynamic contouring errors under high-speed motion. By adding dynamic error models to a simulation, the errors can be clearly displayed on a Z-map model. Hence, it becomes possible to predict under what conditions dynamic errors may occur. Comparing the Z-map model after simulation with the CAD model also makes it possible to find where the dynamic errors occur. This will also allow us to obtain useful information to determine where and when to change the feed rate in order to meet the accuracy requirement.